Constitutive Vagus Nerve Activation Modulates Immune Suppression in Sepsis Survivors - Rana, Minakshi; Fei-Bloom, Yurong; Son, Myoungsun; La Bella, Andrea; Ochani, Mahendar; Levine, Yaakov A.; Chiu, Pui Yan; Wang, Ping; Chavan, Sangeeta S.; Volpe, Bruce T.; Sherry, Barbara; Diamond, Betty (Frontiers in Immunology, 2018)
Patients surviving a septic episode exhibit persistent immune impairment and increased mortality due to enhanced vulnerability to infections. In the present study, using the cecal ligation and puncture (CLP) model of polymicrobial sepsis, we addressed the hypothesis that altered vagus nerve activity contributes to immune impairment in sepsis survivors. CLP-surviving mice exhibited less TNFα in serum following administration of LPS, a surrogate for an infectious challenge, than control-operated (control) mice. To evaluate the role of the vagus nerve in the diminished response to LPS, mice were subjected to bilateral subdiaphragmatic vagotomy at 2 weeks post-CLP. CLP-surviving vagotomized mice exhibited increased serum and tissue TNFα levels in response to LPS-challenge compared to CLP-surviving, non-vagotomized mice. Moreover, vagus nerve stimulation in control mice diminished the LPS-induced TNFα responses while having no effect in CLP mice, suggesting constitutive activation of vagus nerve signaling in CLP-survivors. The percentage of splenic CD4+ ChAT-EGFP+ T cells that relay vagus signals to macrophages was increased in CLP-survivors compared to control mice, and vagotomy in CLP-survivors resulted in a reduced percentage of ChAT-EGFP+ cells. Moreover, CD4 knockout CLP-surviving mice exhibited an enhanced LPS-induced TNFα response compared to wild-type mice, supporting a functional role for CD4+ ChAT+ T cells in mediating inhibition of LPS-induced TNFα responses in CLP-survivors. Blockade of the cholinergic anti-inflammatory pathway with methyllcaconitine, an α7 nicotinic acetylcholine receptor antagonist, restored LPS-induced TNFα responses in CLP-survivors. Our study demonstrates that the vagus nerve is constitutively active in CLP-survivors and contributes to the immune impairment.